Cervical Lymph Node Schwannoma-An Unexpected Diagnosis - Catarina Falcão Silvestre; Joana Almeida Tavares; Dolores López-Presa; Vanessa Rebelo dos Santos; José Rocha; Maria João Bugalho (SAGE Publishing, 2019)
Introduction: Schwannomas-Schwann cells-originating tumors-may develop in many locations. However, primary schwannomas arising within lymph nodes are extremely rare, with only a few cases described to this date in the English literature. For the intranodal location, most of the cases are described in the abdominal cavity. In these cases, clinicians may consider and check for familial disorders, such as neurofibromatosis type 2 (NF2) and schwannomatosis also called neurofibromatosis type 3. Schwannomas are benign neoplasms. Histologically, differential diagnosis for spindle-cell lesions in lymph nodes is important and must be done carefully, mainly because they may be attributable to metastatic disease. We report a case of a primary schwannoma arising in a cervical lymph node. Background: Primary schwannomas arising within lymph nodes are extremely rare, with only a few cases reported. Since they are benign neoplasms, the differential diagnosis with other intranodal spindle cell lesions, mostly malignant, is important. Methods: An asymptomatic 69-year-old woman, previously submitted to left hemithyroidectomy for a benign folicular nodule, underwent thyroidectomy totalization following the identification of a large thyroid nodule in routine evaluation. Results: Gross and microscopic examination and ancillary studies were consistent with the diagnosis of intranodal schwannoma. The patient had acquired bilateral hypoacusia. Therefore, type 2 neurofibromatosis was considered and vestibular schwannomas ruled out. Conclusion: Herein, we present the second case of a primary schwannoma in a cervical lymph node reported so far. The relevance of the differential diagnosis is highlighted.